Myocardial Infarction in the ISCHEMIA Trial: Impact of Different Definitions on Incidence, Prognosis, and Treatment Comparisons. Issue 8 (23rd February 2021) - Chaitman, Bernard R.; Alexander, Karen P.; Cyr, Derek D.; Berger, Jeffrey S.; Reynolds, Harmony R.; Bangalore, Sripal; Boden, William E.; Lopes, Renato D.; Demkow, Marcin; Piero Perna, Gian; Riezebos, Robert K.; McFalls, Edward O.; et al.
Abstract : Background: In the ISCHEMIA trial (International Study of Comparative Health Effectiveness with Medical and Invasive Approaches), an initial invasive strategy did not significantly reduce rates of cardiovascular events or all-cause mortality in comparison with a conservative strategy in patients with stable ischemic heart disease and moderate/severe myocardial ischemia. The most frequent component of composite cardiovascular end points was myocardial infarction (MI). Methods: ISCHEMIA prespecified that the primary and major secondary composite end points of the trial be analyzed using 2 MI definitions. For procedural MI, the primary MI definition used creatine kinase-MB as the preferred biomarker, whereas the secondary definition used cardiac troponin. Procedural thresholds were >5 times the upper reference level for percutaneous coronary intervention and >10 times for coronary artery bypass grafting. Procedural MI definitions included (1) a category of elevated biomarker only events with much higher biomarker thresholds, (2) new ST-segment depression of ≥1 mm for the primary and ≥0.5 mm for the secondary definition, and (3) new coronary dissections > National Heart, Lung, and Blood Institute grade 3. We compared MI type, frequency, and prognosis by treatment assignment using both MI definitions. Results: Procedural MIs accounted for 20.1% of all MI events with the primary definition and 40.6% of all MI events with the secondary definition. Four-year MI rates in patients undergoing revascularization were more frequent with the invasive versus conservative strategy using the primary (2.7% versus 1.1%; adjusted hazard ratio [HR], 2.98 [95% CI, 1.87–4.73]) and secondary (8.2% versus 2.0%; adjusted HR, 5.04 [95% CI, 3.64–6.97]) MI definitions. Type 1 MIs were less frequent with the invasive versus conservative strategy using the primary (3.40% versus 6.89%; adjusted HR, 0.53 [95% CI, 0.41–0.69]; P <0.0001) and secondary (3.48% versus 6.89%; adjusted HR, 0.53 [95% CI, 0.41–0.69]; P <0.0001) definitions. The risk of subsequent cardiovascular death was higher after a type 1 MI than after no MI using the primary (adjusted HR, 3.38 [95% CI, 2.03–5.61]; P <0.001) or secondary MI definition (adjusted HR, 3.52 [2.11–5.88]; P <0.001). Conclusions: In ISCHEMIA, type 1 MI events using the primary and secondary definitions during 5-year follow-up were more frequent with an initial conservative strategy and associated with subsequent cardiovascular death. Procedural MI rates were greater in the invasive strategy and with the use of the secondary MI definition. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01471522. Abstract : Supplemental Digital Content is available in the text.